Informal Support According to Level of Competence Related to Health and Functioning in Quality of Later Life - Rojo-Perez, Fermina; Delagado-Sanz, Concepción; Fernandez-Mayoralas, Gloria; Joao Forjaz, M.; Ahmed-Mohamed, Karim; Martinez-Martin, Pablo; Prieto-Flores, Maria-Eugenia; Rojo-Abuin, Jose-Manuel (Nieformalne wsparcie w zależności od kompetencji dotyczącej zdrowia i funkcjonowania w podeszłym wieku, 2009)
Introduction: An empirical study in the Madrid Region has shown that health, family and social networks are among the most important domains spontaneously self-nominated by aged people to define their Quality of Life. Older adults frequently find, when needed, emotional and/or instrumental support to perform their Activities of Daily Living (ADL) from their spouses, children, other relatives, friends or neighbours. Moreover, among people aged 65 and more, many are caregivers as well. Objective: This work aims at exploring the role of family and social networks as instrumental support to vulnerable or dependent older persons, under the assumption that there are differences in QoL according to the level of competence related to health and functioning and to the role of informal support and socio-demographic characteristics. Data source and methods: The data come from a Survey on Quality of Life in Old Age carried out in 2005, with a representative sample of 499 people aged 65 and over, living in family housing in the Madrid Region (Spain). In order to test whether there are differences in QoL among the older adults according to the level of competence related to health, independence level or functional ability (without or with functional limitation), receiving informal support and socio-demographic characteristics, univariate and multivariate statistical analysis are applied. Results: When analysing functional level in later life, almost a half of the studied population report functional limitation and significant differences in HRQoL are found according to functional state (non-parametric test of Mann-Whitney). Based on a Logistic Regression model, the risk of having functional limitations among the old people in Madrid is higher among men, increasing age, comorbidity and those who perceive their health worse than a year before; having functional limitation is less likely among old people with no health problems. Among old dependent people (47%), more than a half report receiving informal care, and there are significant differences in HRQoL according to informal care received. The probability of receiving informal care when having functional limitations is higher in the oldest age groups and people with the worse health states according to the Euroqol-5D instrument.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 73, s. 64-85